Effects of Cd uptake, translocation and redistribution in different hybrid rice varieties on grain Cd concentration - Qiuhong Luo; Bin Bai; Yunhe Xie; Dongping Yao; Dongmeng Zhang; Zhe Chen; Wen Zhuang; Qiyun Deng; Yinghui Xiao; Jun Wu (Ecotoxicology and Environmental Safety, 2022)
In order to identify the key transport process that determines the Cd concentration in brown rice, this study used 21 hybrid rice varieties as experimental materials and conducted field experiments in Qiyang (cadmium-contaminated site) and Yongding (low-cadmium site). Cd concentrations in 8 organs were measured, and bioconcentration factors and transfer factor were further calculated. The results showed that the Cd concentrations of the organs related to the xylem transport were as follows: root > node > stem > leaf sheath > leaf. In the phloem, the Cd concentrations were as follows: rachis > brown rice > rice husk. And the results of the correlation analysis found that Cd concentration between brown rice and root showed a significant positive correlation in Cd-contaminated site, but no significant correlation in low-cadmium site. Meanwhile, at both experimental sites, the Cd concentration of brown rice showed the most significant correlation with the phloem transfer factor from leaf and leaf sheath to brown rice. Principal Component Analysis (PCA) and stepwise regression analysis likewise found that Cd concentration in leaf and leaf sheath and their phloem transport of Cd to brown rice were significantly and positively correlated with Cd concentration in brown rice. The above results showed that the transport of leaf and leaf sheath to brown rice was a key process, and played a more important role in the accumulation of cadmium in brown rice than in root.